2004
DOI: 10.1074/jbc.m313049200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Annexin A2 by Reversible Glutathionylation

Abstract: The annexin A2-S100A10 heterotetramer (AIIt) is a multifunctional Ca 2؉ -dependent, phospholipid-binding, and F-actin-binding phosphoprotein composed of two annexin A2 subunits and two S100A10 subunits. It was reported previously that oxidative stress from exogenous hydrogen peroxide or generated in response to tumor necrosis factor-␣ results in the glutathionylation of Cys 8 of annexin A2. In this study, we demonstrate that AIIt is an oxidatively labile protein whose level of activity is regulated by the redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 53 publications
2
45
0
Order By: Relevance
“…However, our results indicate that the most efficient way to glutathionylate TRX f in vitro is the use of an oxidant in the presence of GSH, as already observed for other proteins (17). Indeed, exposure of cells to ROS appears to be the more effective mechanism in vivo (15,16). Our data suggest that glutathionylation could be a way of decreasing TRXf activity under conditions of enhanced ROS production.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, our results indicate that the most efficient way to glutathionylate TRX f in vitro is the use of an oxidant in the presence of GSH, as already observed for other proteins (17). Indeed, exposure of cells to ROS appears to be the more effective mechanism in vivo (15,16). Our data suggest that glutathionylation could be a way of decreasing TRXf activity under conditions of enhanced ROS production.…”
Section: Discussionmentioning
confidence: 56%
“…This modification notably occurs in response to enhanced production of reactive oxygen species (ROS) and͞or increases in oxidized glutathione (GSSG). Glutathionylation can protect proteins from irreversible oxidation and͞or modulate their activity (12)(13)(14)(15)(16)(17). Despite its theoretical appeal as a mechanism transmitting oxidative signals under stress, very little is known about glutathionylation in plants.…”
mentioning
confidence: 99%
“…GRX1 and S-glutathionylation are thought to be involved in a variety of cellular events such as signal transduction, stress response, and metabolic regulation, by regulating the redox status of various cellular proteins, including HIV-1 protease 16) , glyceraldehyde-3-phosphate dehydrogenase (GAPDH) 17) , nuclear factor I 18) , ASK1 19) , actin 20) , Ras 21) , tubulin 22) , tau and microtubule-associated protein-2 23) , annexin A2 24) , and protein tyrosine phosphatase 1B 25) . We have also reported that GRX plays an important role in protecting cells from apoptosis by regulating the redox status of Akt/protein kinase B 26) .…”
Section: Introductionmentioning
confidence: 99%
“…In response, the sulfhydryl groups are oxidized to form disulfides in a reaction with the reduced form of glutathione disulfide (GSSG) or converted irreversibly to sulfenic, sulfinic, and sulfonic acid derivatives. 11 S-Glutathionylated proteins reported to date include glyceraldehyde-3-phosphate dehydrogenase, 12 annexin A2, 13 protein kinase C, 14 and carbonic anhydrase III. 15 The S-glutathionylation of proteins is initiated in the presence of GSSG.…”
mentioning
confidence: 99%